Sudden and rapid decline of the abundant marsupial Bettongia penicillata in Australia. Issue 1 (January 2015) - Wayne, Adrian F.; Maxwell, Marika A.; Ward, Colin G.; Vellios, Chris V.; Wilson, Ian; Wayne, Julia C.; Williams, Matthew R.
Abstract The woylie Bettongia penicillata is categorized as Critically Endangered, having declined by c. 90% between 1999 and 2006. The decline continues and the cause is not fully understood. Within a decline diagnosis framework we characterized the nature of the decline and identified potential causes, with a focus on the species' largest populations, located in south-west Western Australia. We described the spatio-temporal pattern of the decline, and several attributes that are common across sites. We categorized the potential causes of the decline as resources, predators, disease and direct human interference. Based on the available evidence the leading hypothesis is that disease may be making woylies more vulnerable to predation but this remains to be tested. No substantial recoveries have been sustained to date, and one of the three remaining indigenous populations now appears to be extinct. Therefore, verifying the factors causing the decline and those limiting recovery is becoming increasingly urgent. Active adaptive management can be used to test putative agents, such as introduced predators. Insurance populations and ecological monitoring should also be included in an integrated conservation and management strategy for the species.